Human Infection Studies and the SARS-CoV-2 Pandemic (Global Journal of Medical Research, 2023)
What could humanity have done better in fighting the SARS-CoV-2 pandemic From a financial and scientific point of view it has done many things right but a crucial ethical question has remained rather unexamined In this paper I argue that controlled human infection studies HIS would have been ethically justifiable and the right way forward in developing a vaccine against Covid-19 The phase 2 3 trials of the vaccines from AstraZeneca Pfizer Biontech and Moderna took between 112 and 196 days Human challenge trials would have taken much less time about 30 days In retrospect these three vaccines could have been launched 82 to 166 days earlier than they actually were If this had happened hundreds of thousands of deaths and millions of hospitalisations worldwide could have been avoided due to the cumulative effect In terms of preparatory measures for the next pandemic the ethical discussion on HIS is of utmost relevance for the well-being of future generations